Hydroarylation reactions of N-acylaminosubstituted tricyclic imides - Gul, Melek; Kulu, Irem; Ocal, Nuket (SCIENCE REVIEWS 2000 LTD, 2013)
The palladium-catalysed hydroarylation of unsaturated N-acylamino-substituted tricyclic imides provided a new stereoselective synthesis of exo-aryl(heteroaryl)-substituted tricyclic N-acylamino imides.
Keywords: tricyclic imides; C-C coupling; heterocycles; POTENTIAL PHARMACOLOGICAL AGENTS; SUBSTITUTED CYCLIC IMIDES; DOMINO-HECK REACTIONS; UNSATURATED DICARBOXIMIDES; EPIBOXIDINE; DERIVATIVES; ANALOGS; EPIBATIDINE; ANTICANCER; Chemistry